A systematic review on best practices of construction waste management in construction project / Noor Rizallinda Ishak, Siti Akhtar Mahayuddin and Hayroman Ahmad - Ishak, Noor Rizallinda; Mahayuddin, Siti Akhtar; Ahmad, Hayroman (2022)
Construction waste management is the process of preventing and diverting construction waste from landfills while utilising recyclable resources. The term best practices refers to the best option among a group of other practices developed for the aim of construction waste management. These best practices can assist construction practitioners in reducing waste in construction project. Hence this paper sets out to analyse the existing literature on best practices of construction waste management in construction project. This paper involved various research designs, and its outcomes are based on the publication standard, specifically ROSES (RepOrting standards for Systematic Evidence Syntheses). Selected articles used two leading databases namely Scopus and Web of Science and one supporting database namely Google Scholar. Based on the thematic analysis, this review has identified seven main themes namely 1) on-site practices; 2) material management; 3) procurement; 4) design; 5) regulation; 6) technology and 7) human resource management. The seven main themes have further produced 31 sub-themes. This paper offered several significant contributions for practical purposes and the body of knowledge. The findings explained the importance of implementing best practices of construction waste management towards sustainable development. This paper also provides useful information for construction practitioner in developing their waste management strategies and benchmarking their waste management performance. Furthermore the findings will also assist construction practitioners in reducing waste generated by construction activities.